GAMBARAN FAKTOR RISIKO PENINGKATAN TEKANAN DARAH PADA REMAJA USIA 12-14 TAHUN (Studi Pada Siswa SMP Islam Al Azhar 14 Semarang) - Dwi Utari Nugroho; Lintang Dian Saraswati; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Hypertension is an increase in blood pressure in the arteries. Hypertension was an increasing of blood pressure in artery. Adolescent who suffered from high blood pressure were likely to undergo it until adulthood. A research conducted in Semarang in 2012 showed that 30,03% of Junior High School adolescents suffer from hypertension. Research in Semarang in 2012 hypertension adolescents was 30.03%. The purpose of this study was to describe the factors associated with blood pressure in in 12-14 years old adolescents in Al Azhar 14 Islamic Junior High School. This study type was descriptive observational with cross sectional design. The population of this study were all students in Al Azhar 14 Islamic Junior High School aged 12-14 years old. 100 samples were chosen by using proportionate stratified random sampling method. Descriptive analysis results showed that prevalence of hypertension was 5% and sistolic hypertension was 5% and diastolic hypertension was 43%. Mean sistolic blood pressure of adolescent is 105,91 mmHg and diastolic blood pressure is 74,63 mmHg.Systolic and diastolic hypertension were mostly found on boys (7.1% and 51,8%), had obesity (18.2% and 68,2%), had sedentary behavior (6.2% and 44,4%), had less physical activity (5.1% and 43,9%), had a habit of frequent consumption of sodium (6.9% and 51,7%), had a habit of frequent consumption of fat (5.7% and 50,9%), had a habit of frequent sugar consumption (5.8% and 51,9%). It was concluded that the occurrence of hypertension was most common in boys, obesity, sedentary behavior > 2 hours, less physical activity, sodiumconsumption habits, fat consumption habits, and habits of sugar consumption. Suggestions for adolescents were to reduce the consumption of sodium, fat and sugar, to do physical activity and to reduce sedentary behavior.